Hepatoprotective Effect of Lactobacillus Plantarum Against Salmonella Typhimurium in Mice - Zedan, Zahraa K (Al-Nahrain Journal of Science, 2011)
This study was designed to investigate the ability of Lactobacillus plantarum as hepatoprotective microorganism against Salmonella typhimurium in mice. Twelve albino mice were divided into 4 groups designated as CC, PC, SC and PS. Each group consisted of 3 mice, and was subjected to the following treatments; CC; this group was used as a control. PC; this group was dosed with 0.1ml of 109 cfu/ml Lb plantarum culture.SC; this group was dosed with 0.1ml. of 2.5×107cfu/ml Sal. typhimurium culture. PS; this group was dosed with 0.1ml of 109cfu/ml Lb. plantarum culture, and infected with 0.1ml of 2.5×107 cfu/ml culture of Sal. typhimurium, then serum levels of Glutamic Pyruvic Transaminase (GPT) and Glutamic Oxaloacetic Transaminase (GOT) of treated mice were measured and histological sections were made from liver to evaluate protective effect of Lb. plantarum . Results showed that mice treated with Lb plantarum exhibited a significant (p≤ 0.05) decrease in serum level of GPT and GOT (43.25 U/L and 95.50 U/L, respectively) in comparison with their levels in serum of control group. Mice infected with Sal. typhimurium showed a significant (p≤ 0.05) increase in serum level of GPT (87.3 U/L), and a significant increase (p≤0.05) in serum level of GOT (227 U/L) in comparison with their levels (55.23 U/L and 113 U/L) in control group. Mice treated with Lb. plantarum and infected with Sal. typhimurium showed a significant (p≤ 0.05) decrease in serum GPT level (47.5U/L) and significant decrease (P≤0.05) in serum GOT level (121 U/L) in comparison with their levels in mice infected with Sal. typhimurium. Histopathological study showed that infection with Sal. typhimurium caused a necrosis, degenerative changes and inflammatory cells infiltration as compared with control while, treatment with Lb plantarum prevented the histopathological effect of Sal. typhimurium on mice liver.